METHODOLOGICAL APPROACHES TO VETERINARY SERVICE EFFICIENCY EVALUATION IN LIVESTOCK - Bannikova, Natalia; Baicherova, Anzhelika (Economics of Agriculture, 2014)
This paper presents the contradiction between modern views on the role of veterinary science from the concept "one health" position, which implies an important role in health assurance and the welfare of the whole veterinary care society, and existing methodological support of its efficiency evaluation. The analysis of existing methods of veterinary attendance efficiency evaluation was conducted on the case of Stavropol Territory and with the help of canonical correlations method their disadvantages were shown. The paper provides rationalization for the need of veterinary science external effect consideration, which operates in healthcare and environmental protection. The procedure for calculating the integral coefficient of veterinary service efficiency was proposed, which allows taking into account the complex of internal and external effects. The integral coefficient may be used in the process of comparative analysis, in the specification of strategic growth priorities, in the motivation system integration of veterinary service employees.